IMPROVING THE ABILITY TO ARRANGE WORDS INTO SENTENCES BASED ON MIDDAY ACTIVITIES BY USING WORD PICTURE CARD MEDIA AT CLASS 1.C SD NEGERI 10 KECAMATAN PINGGIR, KABUPATEN BENGKALIS - Raja Usman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This was classroom action research (CAR) consisting of two cycles. The main focus in this study was arranging words into sentences based on midday activities by using word picture card media. The subjects of this study were students at grade 1.C SD Negeri 10 Pinggir. The purpose of this study was to improve students’ learning outcomes. The average score of students’ learning outcome in the pre-cycle was 31.68, then it increased to 72.68 in cycle I, and 82.80 in cycle II. The minimum achievement criteria set by the school was 70. In the pre-cycle, 57.14% of students did not achieve the KKM while 42.86% achieved the KKM. Then, in cycle I, 35.71% of the students did not achieve the KKM and the remaining 64.29% achieved the KKM; in cycle II, all students or 100% achieved the KKM. Related to changes in students’ behavior toward self-confidence, discipline, and cooperation as well as knowledge of skills in learning, students’ self-confidence in cycle I began to appear with MT at 60.71%, MB at 32.14%, and SM at 7.14%. For discipline, MT was 72.18%, MB was 39.20%, and SM was 17.88%. Meanwhile, for cooperation, MB was 28.57% and SM was 71.43%. In cycle II, for self-confidence, MT and SM were both 50.00%; for discipline, MB was 35.71% and BC was 64.29%; and for cooperation, B was 14.29% and BC was 85.71%. In cycle I, there was only one error (67.86%) and 2–3 mistakes (32.14%). In cycle II, there was only one error (89.29%) and 2–3 mistakes (10.71%). It can be concluded that the use of picture media increased students’ activity and learning outcomes in writing words into sentences at elementary school.